Funcionalidad familiar y estrés académico en estudiantes de enfermería en contexto de pandemia COVID-19 - Azañedo Galdos, Sara Mirella (2022)
The present research with a quantitative, correlational, cross-sectional approach, aims to verify if there is an association between the level of family functionality and academic stress in nursing students in the context of the COVID-19 pandemic. Two instruments were used for data collection; the Smilkstein Family Apgar and the Adaptation of the SISCO SV academic stress questionnaire by Barraza to the context of the COVID-19 crisis. The information was processed and analyzed using Kendall's Tau-c statistical test, the data in relation to family functioning are: 41.2 percent of nursing students presented mild family dysfunction; 37.1 percent normal functionality and 21.8 percent moderate dysfunction. Regarding the level of academic stress, 93.5 percent of nursing students have a medium level of academic stress, followed by 4.7 percent with a low level of academic stress and 1.8 percent with a high level of stress. Therefore, it is concluded that there is no statistically significant association between the level of family functioning and the level of academic stress in Nursing students, which is evidenced by Kendall's Tau C test (0.030, p-value = 0.390). at a significance level of 5%.